Implications of hot chemical–thermal enhanced oil recovery technique after water flooding in shale reservoirs. (November 2020) - Fan, Guangli; Xu, Jin; Li, Meng; Wei, Tao; Nassabeh, Seyed Mohammad Mehdi
Abstract: Due to the applicability of hot water injection in the heavy oil production, it has considered as one of the efficient methods in recovery performances. However, its low viscosity has caused to produce lower oil in shale formations. Therefore, hybrid chemical enhanced oil recovery techniques such as foam injection with sequential carbon dioxide injection would be of important in the heavy oil production. In this paper, we aimed to consider induced hot carbon dioxide–foam enhanced oil recovery technique after water flooding at different temperatures. First, we investigated temperature impact on the resistance factor at different gas–oil ratios (henceforth; GOR). Then, polyacrylamide additive (PAM) at different concentrations were added to the foaming agent to increase the foam stability. Oil recovery factor and water cut were measured for each scenario. According to the results of these experiments, temperature increase would cause to resistance factor increase in which the temperature of 180 ° C has the highest resistance factor. It is about 93%. Moreover, increase of GORs has caused to enhance the resistance factor. Polymer concentration increase has caused to resistance factor increase that is related to the polymer property to enhance the foam stabilization. Consequently, by the increase of temperature, water changes from liquid phase to gas or vapor and this is why it has decreased in the first steps of pore volume injection. Therefore, in the temperature of 180 °C, there is not any water cut in the first period of injection. Furthermore, higher polymer concentration would have an important role on the oil recovery increase.